2008
DOI: 10.1111/j.1570-7458.2008.00723.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovipositional preferences and larval performances of two populations of Indianmeal moth, Plodia interpunctella

Abstract: Oviposition decisions by female insects can determine the survival and fitness of their offspring. In this study, we assessed the larval performance and adult oviposition preferences of two populations of the Indianmeal moth, Plodia interpunctella (Hübner) (Lepidoptera: Pyralidae), one a long‐term laboratory colony and another recently collected from the field. Development assays on a variety of foods were conducted on individual larvae in small shell vials, and data were collected for survival (percent), deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
(55 reference statements)
1
6
0
Order By: Relevance
“…from P. interpunctella females. Nevertheless, P. interpunctella has similar ovipositional preferences for a variety of foods [ 15 , 16 ], so we can expect that the general patterns of oviposition behavior will be similar to what we have described here, irrespective of the type of food. We used different amounts and particle sizes of soybean in our three studies rather than consistently using the same size of food pieces.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…from P. interpunctella females. Nevertheless, P. interpunctella has similar ovipositional preferences for a variety of foods [ 15 , 16 ], so we can expect that the general patterns of oviposition behavior will be similar to what we have described here, irrespective of the type of food. We used different amounts and particle sizes of soybean in our three studies rather than consistently using the same size of food pieces.…”
Section: Discussionsupporting
confidence: 66%
“…Direct lighting as well as light reflected off the white paper facilitated observations of oviposition behaviors within the dish. Soybean was used because an earlier study showed that soybean was a good larval food source that elicited an optimal ovipositional response from adult P. interpunctella females [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low numbers of adult P. interpunctella recovered throughout the later intervals of the experiment may possibly be attributed to the brittle adult corpses being destroyed by larval competition, wanderingstage activity, web-production of subsequent caterpillar generations, crowding, or cannibalism within the conÞnes of jars (Benson 1973, Briggs et al 2000. In addition, low adult numbers may be because of the pecan "meal" produced by feeding being of inadequate size to complete reproduction in P. interpunctella (Sambaraju and Phillips 2008).…”
Section: Discussionmentioning
confidence: 95%
“…In addition to the odour component of food source, there is evidence that tactile and gustatory qualities are also important for oviposition stimulation (Mowery et al 2002;Nansen and Phillips 2003). It has previously been shown that females are able to discriminate between individual odour stimuli (Nansen and Phillips 2003;Sambaraju and Phillips 2008), and that cereal products, nuts and dried fruits are among the most attractive food products for P. interpunctella (Mohandass et al 2007). For this reason, it is not surprising that unpacked cereal-fruit bars stimulated females to an oviposition, as in the no-choice test the vast majority ([ 98%) of eggs laid by females were placed on the bar and only small fraction was placed on the floor.…”
Section: Discussionmentioning
confidence: 99%